Cardiovascular Effects of Sympathetic Blocking Receptor Beta - Rubio, Enrique (1964)
The wide range of pharmacological and therapeutic action featuring catecholamines, both in their actions and reactions, every day is much higher. Each new discovery opens new horizons of research and practical application. Studies to elucidate the mechanisms by which they act, have led to many hypotheses and theories. Ahlquist (1), in 1948, presented the Theory of Sympathetic Receptors "very Adrenergic explaining this intricate problem." This work contributes to the study of this theory, concerning the discovery of Alderlín (8), a substance that would block beta receptors.